A Conceptual Paper on CAIRA as a Sustainable Approach to Future Learning in Malaysia. - Dayang Kartini, Abang Ibrahim; Nurain Shavika, Ahmad Shauffi (BAHAGIAN PEMBANGUNAN KURIKULUM, Kementerian Pendidikan Putrajaya, 2025)
Malaysia’s national education policy has long prioritized standardized assessments, often at the expense of holistic, real-world skill development. To address the demands of the 21st century, this conceptual paper proposes the CAIRA (Connection, Acquisition, Integration, Reflection, Application) as a transformative approach for curriculum reform. Aligned with Malaysia MADANI’s values and Sustainable Development Goal 4 (Quality Education), CAIRA emphasizes competency-based learning, interdisciplinary integration, and the cultivation of altrocentric learners, an individual who prioritize empathy, sustainability, and collective well-being. The conceptual paper (1) proposes CAIRA as a holistic approach for competency-based, values-driven education (2) align CAIRA with National Curriculum Policy to demonstrate its relevance to national and global priorities (3) outline implementation strategies and policy recommendations for sustainable curriculum reform. The derived approach will summarize stakeholders’ desires on the insights of skills gap as it can serve as the template to develop a generic pedagogical approach that creates new opportunities for teaching and learning. It can also be used to enhance the existing functionalities in the approach of a new curriculum. By bridging policy, pedagogy, and societal needs, CAIRA offers a roadmap for developing future-ready, ethical leaders in Malaysia’s education system.